2022
DOI: 10.3390/buildings12030348
|View full text |Cite
|
Sign up to set email alerts
|

New Optimal Supply Air Temperature and Minimum Zone Air Flow Resetting Strategies for VAV Systems

Abstract: Buildings account for a large portion of the total energy use in the US; therefore, improving the operation of typical variable-air-volume (VAV) systems in buildings can provide a tremendous economic opportunity. ASHRAE Guideline 36 recommends a resetting strategy for supply air temperature (SAT) for VAV systems based on outside air temperature. However, this strategy may not produce optimal performance, particularly when simultaneous cooling and heating occurs in zones. In addition, there is no strategy recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Equations ( 5) and ( 6) can be organized into the simpler expression as shown in equations (7) and (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equations ( 5) and ( 6) can be organized into the simpler expression as shown in equations (7) and (8).…”
Section: Methodsmentioning
confidence: 99%
“…The airflow was assumed to enter the adherent jet zone. From equation (7), the velocity decay coefficient K is only related to the adherent jet zone, and the range of the free jet and transition zone are uniformly attributed to the constant x 0 . In order not to affect the overall data fitting accuracy, point 1 was removed when calculating the velocity decay curve.…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, resetting the SAT as a function of OAT may not be the best strategy as there may be zones in cooling even during colder seasons. As a response, Nassif [27] has proposed using zone heating or cooling control loops to reset the supply air temperature. In this strategy, the number of zones in cooling or heating at any time is counted, and the zone value is assigned to be 1 (one) if the zone is in a cooling or dead band.…”
Section: Proposed Supply Air Temperature (Sat) Reset Strategymentioning
confidence: 99%
“…Saloux and Zhang [96] evaluated the impact of a supply air temperature reset strategy based on outdoor air enthalpy for an existing large commercial building; they found that the building cooling load could be decreased by 13%, resulting in a 9% reduction in cooling system electric energy. Nassif et al [107] built upon G36 to develop new strategies to reset supply air temperature and zone minimum airflow rate setpoints for typical VAV systems; the authors showed a potential of 2-6% fan energy decrease and 8-34% heating load reduction. Lu et al [108] compared the performance of G36 for supply air temperature and static difference pressure setpoints with intelligent controllers (optimization-based controller and deep reinforcement-learning-based controller) for a simulated medium-sized office building with a multi-zone variable air volume cooling system.…”
Section: High-performance Control Sequencesmentioning
confidence: 99%